Biotechnological purification of a β-fructofuranosidase (β-FFase) from Aspergillus tamarii kita: Aqueous two-phase system (PEG/Citrate) and biochemical characterization. (August 2021) - Matias da Silva Batista, Juanize; Pedrosa Brandão-Costa, Romero Marcos; Barbosa Cardoso, Kethylen Barbara; Nascimento, Thiago Pajeú; Albuquerque, Wendell W.C.; Carneiro da Cunha, Márcia Nieves; Porto, Camila Souza; Bezerra, Raquel Pedrosa; Figueiredo Porto, Ana Lucia
Abstract : β-fructofuranosidases (EC3.2.1.26) are members of the GH32 family of glycoside hydrolases, which include more than 390 enzymes of vegetable and microbial origins, used in several biotechnological applications. Thus, this research aimed to produce a β-fructofuranosidase obtained by Aspergillus tamarii through solid state fermentation, and to purify by Aqueous Two-Phase System (ATPS). Summary results presented the optimal parameters to produce the β-fructofuranosidase used wheat bran as a substrate at 30 °C for 48 h, and purification process using ATPS with polyethylene glycol and sodium citrate (PEG/sodium citrate), where the β-fructofuranosidase preferably partitioned to the salt-rich phase, the best run (24% of PEG 400, 20% sodium citrate, pH 8) which presented a higher purification factor 6.42 with 12.39 U/mL activity and 352% yield. Optimum parameter was pH 5.15 and temperature of 55 °C, respectively. The purified enzyme showed excellent thermal stability and exhibited a half-life of 60 min at 65 °C. Kinetics results for enzyme showed for Sucrose substrate the enzyme showed Km of 42.9 ± 2.21 mM and Vmax of 180.2 ± 2.8 μM min −1  mg −1 of protein. Although Vmax was the highest for 1-Kestose (219.4 ± 2.7 μM min −1  mg −1 of protein) the preferred substrate of Aspergillus tamarii β-fructofuranosidase ( β-FFase ) was Nystose (Km of 3.8 ± 0.15 mM). SDS-PAGE revealed a single band of protein at ~66 kDa. Finally, this study demonstrated the potential of ATPS to purify a β-fructofuranosidase with application in biotechnological field aiming to functional foods. Highlights: Aqueous Two-Phase System (ATPS) showed high efficiency to purify β-FFase. SDS-PAGE revealed a single band of protein at ~66.0 kDa. The purified enzyme showed excellent thermal stability and exhibited a half-life of 60 min at 65 °C. Chemical susceptibility of β-FFase activity was stable in the presence of ions. The US exposure increased the activity of β-fructofuranosidase about 70%.